2021
DOI: 10.1538/expanim.20-0014
|View full text |Cite
|
Sign up to set email alerts
|

The sirtuin 1 activator SRT1720 alleviated endotoxin-induced fulminant hepatitis in mice

Abstract: The metabolic sensor sirtuin 1 (SIRT1) also functions as a checkpoint in inflammation, and SRT1720 is a highly active and selective SIRT1 activator shown to alleviate inflammatory injury in several recent experimental studies. In the present study, the potential effects and underlying mechanisms of SRT1720 on lipopolysaccharide (LPS)-induced fulminant hepatitis in D-galactosamine (D-Gal)-sensitized mice were investigated. The results indicated that treatment with SRT1720 inhibited LPS/D-Gal-induced elevation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“… Kemelo et al (2014) demonstrated a reduction in SIRT1 levels during lipopolysaccharide (LPS)-induced ALI, leading to impaired hepatic function. Subsequently, Zhou et al (2021) corroborated the protective effects of SIRT1 in ALI models. While the majority of investigations have demonstrated the ameliorative impact of SIRT1 activation on liver injury, certain studies have reported a contrasting perspective, suggesting that SIRT1 may contribute to disease progression and exacerbate tissue damage ( Cui et al, 2016 ).…”
Section: Survey Methodologymentioning
confidence: 64%
“… Kemelo et al (2014) demonstrated a reduction in SIRT1 levels during lipopolysaccharide (LPS)-induced ALI, leading to impaired hepatic function. Subsequently, Zhou et al (2021) corroborated the protective effects of SIRT1 in ALI models. While the majority of investigations have demonstrated the ameliorative impact of SIRT1 activation on liver injury, certain studies have reported a contrasting perspective, suggesting that SIRT1 may contribute to disease progression and exacerbate tissue damage ( Cui et al, 2016 ).…”
Section: Survey Methodologymentioning
confidence: 64%
“…After equilibrating for 10 min at room temperature, TUNEL reaction solution was added for incubation. After 1 h, the nucleus was re-stained with DAPI, and finally the film was taken 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Although the direct effect of activating SIRT1 has been questioned previously [ 62 ], its biological functions in treating different disease models have been intensively studied. For instance, it has been shown to treat cancer [ 10 ], inflammation [ 33 ], ischemia [ 82 ], hepatitis [ 96 ], osteoarthritis [ 59 ], and neurodegeneration [ 6 ], such as Alzheimer's disease. However, the effect of SRT1720 on PD has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%